Dukungan Sosial Guru Bimbingan Konseling terhadap Kematangan Karir Siswa di Sekolah Menengah Atas - Jalal, Novita Maulidya (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine the social support provided by Guidance Counseling Teachers (BK) on the Career Maturity of High School Students or equivalent. The method in this research is library research which uses 9 scientific articles related to social support, guidance and counseling teachers, and career maturity of high school students. The results of this research show that BK teachers provide information services to students who really need services so that they can maximize their learning process and be enthusiastic about achieving their dreams or desired careers. Through career guidance, it can be a bridge for students to get closer and get to know the world of work and the things that must be prepared so that students are able to plan the careers needed in the era of society 5.0. The BK Teacher's efforts include providing individual counseling services, developing group guidance, providing support to students, completing facilities, providing systematic and sustainable training that suits the potential needs of students at school. Additionally, before deciding on an academic or non-academic career path, it is important for students to complete an interest test. The conclusion of this research is that social support from guidance and counseling teachers can support the career maturity of high school students. The implication of this research is that students can use the services of guidance and counseling teachers to support career maturity for the students' future